SCREENING OF GENES RESPONSIBLE FOR β-GLUCAN SYNTHESIS IN GRAIN VARIETIES - Ismagulova, G.A.; Baizhumanova, S.S.; Iskakova, G.A.; Baisaparova, D.O.; Mendesh, A.M.; Tussipova, A.A.; Skiba, Yu.A.; Maltseva, E.R.; Naizabayeva, D.A.; Esimbekova, M.A.; Mukin, K.B. (Eurasian Journal of Applied Biotechnology, 2022)
Currently, β-glucan has a great importance for human life. Because it reduces the risks of many chronic diseases such as diabetes, cancer and digestive disorders. Due to these properties, β-glucan is a natural substance that can be used in pharmaceutical preparations for the prevention and treatment of many chronic diseases. Therefore, an analysis was made for crops rich in sources of β-glucans - 100 varieties of wheat, 50 varieties of barley and 50 varieties of oats, and a collection of genomic DNA was made. Each variety was screened to identify the genes responsible for the synthesis of β-glucans. In the frames of this study, 10 genes were considered. As a result, these genes have been identified in barley, wheat, and oat varieties. For the isolation of β-glucan, the methods of acid extraction, microwave, and heating at high temperature were used. A modified method for isolating β-glucan from oatmeal was developed. According to the results, the acid extraction method proved to be more effective. It is easy to obtain pure β-glucan by this method, and the use of citric acid is safer and more affordable than conventional acids. The improved acid extraction method showed that the concentration of pure β-glucan per 10 g of wheat grain was 66.6%, and the total yield of β-glucan extract increased to 11.3%.